2020
DOI: 10.29333/ajqr/8243
|View full text |Cite
|
Sign up to set email alerts
|

Drug Trafficking on Darkmarkets: How Cryptomarkets are Changing Drug Global Trade and the Role of Organized Crime

Abstract: Drug trafficking on darknet based marketplaces has become a highly concerning topic in law enforcement activities, recently. Even though Darkmarkets represent only a tiny fraction of the global drug trade, they are changing the drug markets social networks, introducing a new paradigm of the link between vendors and buyers of drugs. The aim of this study is to critically review the darkmarkets' ecosystem and the previous literature regarding these new marketplaces, trying to investigate how the drug trade is ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…However, some studies have shown that in recent years recreational drug users changed their purchasing method by using the Internet, especially the Darknet, to provide anonymity, safety, and social distancing (Eligh, 2020). Thus, the Internet has become a trending marketplace for drug dealers and buyers, and drug distribution networks (Bertola, 2020). However, this study showed that none of the participants bought drugs from the Internet during the pandemic.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, some studies have shown that in recent years recreational drug users changed their purchasing method by using the Internet, especially the Darknet, to provide anonymity, safety, and social distancing (Eligh, 2020). Thus, the Internet has become a trending marketplace for drug dealers and buyers, and drug distribution networks (Bertola, 2020). However, this study showed that none of the participants bought drugs from the Internet during the pandemic.…”
Section: Discussionmentioning
confidence: 67%
“…Nevertheless, law enforcement agencies still have tactical advantages in combating Darknet illegal activities, especially detecting postal services, which is the main distribution tool of the Darknet vendors besides traditional investigation tools and technics (Weber & Kruisbergen, 2019). Therefore, law enforcement agencies should develop better strategies rather than shutting down those websites because those virtual shops will be opened under different names on other platforms (Bertola, 2020; United Nations Office on Drugs and Crime, 2018). In fact, the Darknet's closure with the previous operations did not affect more than half of the Darknet users, and it is growing swiftly (United Nations Office on Drugs and Crime, 2018).…”
Section: Policy Recommendationsmentioning
confidence: 99%